Differentiation of the content of chlorophyll, nitrogen and phosphorus in soybean leaves of different tiers - Razumenko, J. L. (AgroChemistry and Soil Science, 2021)
The article presents the results of determining the content of chlorophyll, nitrogen and phosphorus in the leaves of different tiers in soybean plants. The results of testing the working hypothesis about the relationship between chlorophyll content and nutrients are shown and data on the dynamics of their content in soybean leaves in the phases of bean formation, grain filling and the beginning of physiological maturity are demonstrated. The study performed during 2016 and 2017 in the field small-scale experiment of the Department of Agrochemistry of Kharkiv National Agrarian University named after V.V. Dokuchaev in the Kharkiv region of Ukraine. The soil is typical medium loam chernozem (Haplic Chernozem) with a humus content of 5.5–6.1 %, easily hydrolyzed nitrogen – 5 mg / 100 g, mobile phosphorus – 7 mg / 100 g of soil. Soybean seeds treated with the bacterial preparation rhizohumin before sowing. The content of chlorophyll in the leaves of plants determined by colorimetric method after extraction with ethyl alcohol; the total content of nitrogen and phosphorus in the plant samples is also colorimetric after burning the sample in sulfuric acid by the method of wet ashing. The results showed that during all the controlled phases of ontogenesis, the young leaves of the upper tier contained the most chlorophyll, nitrogen and phosphorus, and the leaves of the lower tier contained the least. The highest content of chlorophyll, nitrogen and phosphorus recorded in the leaves of the upper tier in the phase of bean formation, the lowest - in the leaves of the lower tier at the beginning of physiological maturity. No significant difference found between the control variant and the variants with the use of fertilizers. The method of applying the same dose of mineral fertilizers also did not significantly affect the studied indicators. This stated the presence of a characteristic feature of the accumulation and reutilization of nutrients in the leaves of different ages, located on different parts of soybean stems. A close direct correlation was found between the content of chlorophyll in soybean leaves and the content of nitrogen (r = 0.85) and phosphorus (r = 0.76). There is also a direct relationship between the content of nitrogen in the leaves of all tiers and the phosphorus content (r = 0.80).